2017
DOI: 10.3892/or.2017.6088
|View full text |Cite
|
Sign up to set email alerts
|

miR-16 mimics inhibit TGF-β1-induced epithelial-to-mesenchymal transition via activation of autophagy in non-small cell lung carcinoma cells

Abstract: Autophagy is critical for the metastasis of cancer cells through induction of epithelial-to-mesenchymal transition (EMT). Activation of TGF-β signaling plays a key role in regulating autophagy. miR-16 may be associated with non-small cell lung carcinoma (NSCLC) progression. However, the role of miR-16 in NSCLC cell autophagy in the presence of TGF-β and the underlying mechanism are still unclear. To test whether miR-16 targets ATG3 which is involved in autophagy of NSCLC cells, we studied the expression levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
1
23
1
Order By: Relevance
“…dre-miR-16b was up-regulated in cold acclimation in the present study, which is consistent with the report that the expression of miR-16 increases in platelets under cold-storage conditions [46]. miR-16 mimics can activate autophagy in non-small cell lung carcinoma cells [47]. miR-16-5p also shows protective roles in LPS-induced A549 cell injury [48].…”
Section: Discussionsupporting
confidence: 92%
“…dre-miR-16b was up-regulated in cold acclimation in the present study, which is consistent with the report that the expression of miR-16 increases in platelets under cold-storage conditions [46]. miR-16 mimics can activate autophagy in non-small cell lung carcinoma cells [47]. miR-16-5p also shows protective roles in LPS-induced A549 cell injury [48].…”
Section: Discussionsupporting
confidence: 92%
“…In the wounds treated with miR-16-5p, inflammation and angiogenesis were not affected, while collagen deposition was reduced. Interesting, several studies reported that miR-16-5p could suppress TGF-β signaling pathway 47 - 48 , which is closely associated with collagen deposition and hypertrophic scar formation. Thus, further studies are required to explore the possibility of miR-16-5p affecting scar formation during wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the NSCLC microenvironment, tumor-derived TGF-β can also increase miR-183, which can decrease DNAX activating protein 12 kDa (DAP12) (a protein required for NK cell cytotoxicity functions), ultimately inhibiting tumor-infiltrating NK cell activities to promote immunosuppression [140], while miRNAs and lncRNAs can also exhibit opposite effects on lung cancer metastasis. MiR-132 [77], miR-203, miR-145 [78], miR-205 [79], miR-124 [80], miR-422a [17], miR-196b [82], miR-940 [83], miR-22 [84], miR-200a, miR-200c [85,86], miR-145, miR-497 [87], miR-149 [88], miR-134 [89], miR-133 [90], miR-29c [91], miR-16 [94], miR-129 [96], miR-485-5p [97], miR-3127-5p [98], and LINP1 [121] can suppress TGF-β signaling-regulated EMT. MiR-3607-3p [99], miR-206, miR-140 [100], miR-136 [102], miR-133a [103], miR-143 [104], miR-886-3p [105], HAND2-AS1 [119], linc01186 [120], ANCR [122], and NKILA [123] can repress TGF-β signaling-modulated lung cancer cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-16 mimics were transfected into A549 cells to increase their expression levels. Up-regulated miR-16 can activate autophagy to inhibit TGF-β1-induced EMT [94].…”
Section: Mir-16mentioning
confidence: 99%